2022
DOI: 10.1097/mco.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effects of a Mediterranean diet: a review

Abstract: Purpose of reviewChronic noncommunicable diseases remain the leading cause of morbidity and mortality worldwide and the majority are preventable with a healthy diet and lifestyle, but controversy remains as to the best approach. Greater adherence to a traditional Mediterranean diet has consistently been associated with lower morbidity and mortality from cardiovascular disease, diabetes and many cancers, and lower all-cause mortality. Despite the well known benefits on chronic disease risk there remains some sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
0
42
0
Order By: Relevance
“…Multiple components of the Mediterranean diet may contrast factors associated with age-related muscle strength decline, including malnutrition, oxidative stress, inflammation, endothelial dysfunction, and insulin resistance ( Figure 2 ) [ 65 , 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple components of the Mediterranean diet may contrast factors associated with age-related muscle strength decline, including malnutrition, oxidative stress, inflammation, endothelial dysfunction, and insulin resistance ( Figure 2 ) [ 65 , 66 , 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet supplies a plethora of vitamins (e.g., β-carotene, vitamin C, vitamin E), minerals, and polyphenols, with antioxidant, anti-inflammatory, and pro-autophagic properties [ 67 , 70 , 71 , 72 ]. For instance, the PREvencion con DIeta MEDiterranea (PREDIMED) study found a decrease in inflammatory biomarkers, such as interleukin 6, C-reactive protein, and leukocyte adhesion molecules, in participants with higher Mediterranean diet adherence [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring common anti-inflammatories are found in pomegranates, medicinal plants, vitamin D, vitamin C, a Mediterranean diet and extra-virgin olive oil, flavonoids found in fruits, curcumin, resveratrol, aged garlic extract, walnuts, marine carotenoid astaxanthin found in seafood, omega-3 fatty acids, caffeine, and manuka honey ( Almasaudi et al, 2017 ). Ingestion of these foods reduce chronic inflammation and neuroinflammation ( Rekatsina et al, 2020 ; Di Majo et al, 2022 ; Itsiopoulos et al, 2022 ). These (neuro)inflammation reducing foods could be part of the prevention and treatment of neurodegenerative and psychiatric disorders, however, clinical studies are needed.…”
Section: Risk and Protective Factors For Neuroinflammation In Neurode...mentioning
confidence: 99%
“…High intake of dietary fiber and antioxidant compounds shows synergistic beneficial anti-inflammatory effects, especially within the microscopic intestinal barrier and the gut microbiome [ 112 , 113 ]. The Mediterranean diet has in general a strong anti-inflammatory effect [ 114 ]. The dominant anti-inflammatory ingredients in this diet are omega-3 fatty acids, olive oil and phenolic compounds, as well as fiber and a low degree of food processing [ 112 , 114 , 115 ].…”
Section: Nutrition—what Is Beyond the Obvious?mentioning
confidence: 99%
“…The Mediterranean diet has in general a strong anti-inflammatory effect [ 114 ]. The dominant anti-inflammatory ingredients in this diet are omega-3 fatty acids, olive oil and phenolic compounds, as well as fiber and a low degree of food processing [ 112 , 114 , 115 ].…”
Section: Nutrition—what Is Beyond the Obvious?mentioning
confidence: 99%